2020
DOI: 10.1016/j.envsci.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent environmental plan for sustainable regionalisation policies: The case of Ukraine

Abstract: This paper introduces an environment-driven, artificial intelligence model for sustainable policymaking in European countries, with a focus on Ukraine. It develops regional clusters using artificial neural networking; then, it dynamically optimises budgeting allocations. It is a hybrid, environment-driven model that clusters regionalised-data using Kohonen's self-organising map and optimises budget allocations using the simplex-modified distribution method (U-V MODI). Model benefits focus on regional public po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Zhao et al (2022) found a remarkable “U-shaped” contribution of AI to GTFP and found that increasing AI levels in resource-rich areas improved GTFP [ 18 ]. The research on AI and government environmental governance systems is mostly explored in terms of the application of AI technologies in environmental modernization [ 19 , 20 , 21 ], ensuring that emerging technologies such as AI are fully utilized by building new frameworks, policies, and governance [ 22 ]. Current scholarship on GTFP still focuses on policy evaluation and production drivers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2022) found a remarkable “U-shaped” contribution of AI to GTFP and found that increasing AI levels in resource-rich areas improved GTFP [ 18 ]. The research on AI and government environmental governance systems is mostly explored in terms of the application of AI technologies in environmental modernization [ 19 , 20 , 21 ], ensuring that emerging technologies such as AI are fully utilized by building new frameworks, policies, and governance [ 22 ]. Current scholarship on GTFP still focuses on policy evaluation and production drivers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%